Metode dan Strategi Pembelajaran dalam Pendidikan Islam - Mudarti, Hasni; Fatrisna, Yuli; Sesmira, Meli; Amra, Abhanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to find out the learning methods and strategies in Islamic Education. This study uses a literature review approach. Literature reviews focus on the analysis and synthesis of relevant academic sources, such as journal articles, books, and conference proceedings, to gather comprehensive insights into effective teaching and learning practices in the context of Islamic education. The selection of literature is guided by certain inclusion criteria, prioritizing scholarly works published in the last decade and that directly address the methodology of education in Islamic teachings. Data analysis is carried out by a systematic process in identifying, categorizing, and comparing various strategies and methods used in the Islamic educational environment. The results of the analysis show that methods and strategies are a way taken to achieve a goal. An active and creative teaching method or learning method is a way used by a teacher in delivering material or related to Islamic learning to students or students by using various active and creative ways so that the goals of an education, especially in delivering learning material, can be achieved effectively and efficiently.